The Impact of Healthcare Pressures on the COVID-19 Hospitalisation Fatality Risk in England - Jonathon Mellor; Owen Jones; Thomas Ward (Journal of Epidemiology and Global Health)
Abstract Background As the impact of the SARS-CoV-2 pandemic extends into 2023 and beyond, the treatment and outcomes of infected patients continues to evolve. Unlike earlier in the pandemic there are now further infectious disease pressures placed on hospitals, which influence patient care and triage decisions. Methods The manuscript uses individual patient records linked with associated hospital management information of system pressure characteristics to attribute COVID-19 hospitalisation fatality risks (HFR) to patients and hospitals, using generalised additive mixed effects models. Results Between 01 September 2022 and 09 October 2023, the COVID-19 hospitalisation fatality risk in England was estimated as 12.71% (95% confidence interval (CI) 12.53%, 12.88%). Staff absences had  an adjusted odds ratio of 1.038 (95% CI 1.017, 1.060) associated with the HFR when accounting for patient and hospital characteristics. Interpretation This observational research presents evidence that a range of local hospital effects can have a meaningful impact on the risk of death from COVID-19 once hospitalised and should be accounted for when reporting estimates. We show that both the patient case mix and hospital pressures impact estimates of patient outcomes.